Study on Digitization of Special Materials: Expanding Access to Rare and Fragile Resources through Digitization (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Digitization has removed physical barriers to the discovery and application of rare and fragile resources and those recorded in a format which is difficult to access. Access to rare manuscripts, photographs, maps, archival documents, and museum objects sometimes limited because of their value andor fragile nature. Digitization not only expands the reach of these materials to researchers, students, and the general public, but also enhances the visual quality of faded and illegible documents to a readable form.